(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Non-lichenized ostropalean fungi have been poorly studied in Ukraine. The paper contains data on a new for Ukraine and worldwide rare species Schizoxylon centaureae Bres., found on the territory of Regional Landscape Park ‘Tiligulsky’. Characteristic features of this species include filiform spores, which disintegrate onto fragments, and its association with dead stems of Centauria sp and Asphodelus sp. The article contains original illustrations and description of the species. Since this species has been so far known only from Portugal and Greece, our finding of S. centaureae in Ukraine substantially alters a modern concept of its distribution.